Les origines de la vie : sciences, légende et poésie - Wanlin, Nicolas (Studia Romanica Posnaniensia, 2020)
Faced with the scientific hypotheses of the 18th and 19th centuries on the origins of life, some authors try to maintain the creationist imagery while others develop representations of the gradual emergence of life forms from inert matter (heterogeny). The divide is not between the scientific and the literary: what is most remarkable is the pooling of all resources, the borrowing from various disciplines to put words to the emergence of life. This mix of science, poetry, myth and observation, which can be likened to the category of the legendary, shows that science and the humanities dialogue and interpenetrate despite ideological and religious obstacles, and recalls the unity of the cultural whole.